2017
DOI: 10.1007/978-3-319-59448-4_30
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Post-Ablation Outcome in Atrial Fibrillation Using Shape Parameterization and Partial Least Squares Regression

Abstract: Abstract.To analyze left atrial remodeling may reveal shape features related to post-ablation outcome in atrial fibrillation, which helps in identifying suitable candidates before ablation. In this article, we propose an application of diffeomorphometry and partial least squares regression to address this problem. We computed a template of left atrial shape in control group and then encoded the shapes in atrial fibrillation with a large set of parameters representing their diffeomorphic deformation. We applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The left atrial sphericity-a measure of how closely the atrium resembles a sphere-was introduced by Brisbal et al [6] to quantify remodeling of atrial morphology by MRI and to predict post-ablation recurrence. Jia et al [3], mapped diffeomorphic features of patients' atrium on pre-ablation images relative to a constructed atlas to predict AF recurrence using a partial least square fitting. In a recent study by Bieging et al [22], a particle based modeling (PBM) approach from cardiac magnetic resonance scans done in the DE-MRI-Guided Ablation vs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The left atrial sphericity-a measure of how closely the atrium resembles a sphere-was introduced by Brisbal et al [6] to quantify remodeling of atrial morphology by MRI and to predict post-ablation recurrence. Jia et al [3], mapped diffeomorphic features of patients' atrium on pre-ablation images relative to a constructed atlas to predict AF recurrence using a partial least square fitting. In a recent study by Bieging et al [22], a particle based modeling (PBM) approach from cardiac magnetic resonance scans done in the DE-MRI-Guided Ablation vs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified left atrial measurements such as volume [2][3][4], anterior-posterior (AP) diameter [5], and atrial sphericity [6] as predictors of AF recurrence. However, there is a lack of consensus on the strength of these individual biomarkers in gauging the risk of AF recurrence.…”
mentioning
confidence: 99%
“…Thus, the prediction for each patient was built from a model learned from a series of shapes that did not comprise the patient’s own LA shape. To analyze shape features that are independent from atrial size and AF persistence, we separated the analysis into 2 sequential partial least squares regressions 16 : the first one to remove the shape variations that are linearly related to LA volume and AF persistence, and the second one to compute the shape patterns that are linearly related to postablation recurrence. This model (implemented in Matlab2017a) allowed us to provide each patient with an LA shape score normalized to the range from 0 to 1, according to the proximity between the studied patient shape and the shape patterns associated with recurrence.…”
Section: Methodsmentioning
confidence: 99%